LEVEL STRUCTURE OF XE-126 - POPULATION OF LOW-SPIN LEVELS IN THE DECAY OF 1+ CS-126 AND THEORETICAL DESCRIPTION OF ADJACENT EVEN-EVEN XE NUCLIDES - Mantica, P; Zimmerman, B; Walters, W; Rikovska, J; Stone, N (1992)
The low-spin structure of Xe126 has been investigated following the decay of 1.6-min 1+ Cs126. Gamma-ray singles, gamma-gamma coincidences, and conversion-electron spectra have been measured. Several new levels have been identified and some new spins and parities have been suggested. The structure of Xe126 and adjacent Xe nuclides has been investigated through interacting boson model-2 (IBM-2) calculations. The results of these calculations are discussed along with a number of other calculations of the structure of even-even Xe nuclides. Both these IBM-2 calculations and the total Routhian surface calculations suggest notable changes in structure for Xe130. © 1992 The American Physical Society.